2020
DOI: 10.2174/0929867325666181001112226
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Anti-diabetic Properties of Chalcones

Abstract: : The use of anti-diabetic drugs has been increasing worldwide and the evolution of therapeutics has been enormous. Still, the currently available anti-diabetic drugs do not present the desired efficacy and are generally associated with serious adverse effects. Thus, entirely new interventions, addressing the underlying etiopathogenesis of type 2 diabetes mellitus, are required. Chalcones, secondary metabolites of terrestrial plants and precursors of the flavonoids biosynthesis, have been used for a long time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 98 publications
0
42
0
Order By: Relevance
“…Chalcone derivatives bearing a scaffold composed of two benzene moieties connected by an α,β‐unsaturated carbonyl bridge are known to exhibit a wide range of pharmacological activities 1–4 . In addition, they have been used as important precursors for a variety of new drug candidates, including flavonoids and isoflavonoids 5–7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chalcone derivatives bearing a scaffold composed of two benzene moieties connected by an α,β‐unsaturated carbonyl bridge are known to exhibit a wide range of pharmacological activities 1–4 . In addition, they have been used as important precursors for a variety of new drug candidates, including flavonoids and isoflavonoids 5–7 .…”
Section: Introductionmentioning
confidence: 99%
“…Chalcone derivatives bearing a scaffold composed of two benzene moieties connected by an α,β-unsaturated carbonyl bridge are known to exhibit a wide range of pharmacological activities. [1][2][3][4] In addition, they have been used as important precursors for a variety of new drug candidates, including flavonoids and isoflavonoids. [5][6][7] It is well-known that the pharmacological activity of a compound is greatly influenced not only by the basic skeleton of the compound but also by the electronic property and size of functional groups attached to the skeleton.…”
Section: Introductionmentioning
confidence: 99%
“…[13] The antidiabetic activity of the chalcones was most prominent Abbreviations: DPPH, 2,2-diphenyl-1-picryl-hydrazyl-hydrate.. from the extensive range of activities, and many key structural features are already acknowledged in the literature. [14] Diabetes mellitus (DM) is a prevalent global burden of disease now. It is the third leading cause of mortality worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the currently available antidiabetic drugs do not present the desired efficacy and are generally associated with serious adverse side effects. [14] As stated above, vanadium complexes and chalcones both induces great therapeutic potential, but an area of complexation of vanadium metal with chalcones has been less explored. In 2017, Atlam et al [23] synthesized the vanadium complex with DMATP chalcone, and complex was found to possess great deal of DNA binding and antimicrobial potential but did not study its antidiabetic potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation